Ethnicity as a modifier of the association between breastfeeding and distal sensory polyneuropathy in postmenopausal obese women - Jiayu Li; Somsook Santibenchakul; Sukanya Chaikittisilpa; Harnam Kaur; Unnop Jaisamrarn (Clinical Epidemiology and Global Health)
Purpose: We aimed to examine whether ethnicity moderates the association between breastfeeding and distal sensory polyneuropathy in postmenopausal obese women in the United States. Methods: In this cross-sectional study, postmenopausal obese women aged 40 and over were included. Women with major chronic diseases, foot amputation, or insufficient health information were excluded. Distal sensory polyneuropathy was measured using a 10-g monofilament test, and self-reported breastfeeding data were collected based on responses to a brief questionnaire. Multivariable logistic regression was used to examine the association between breastfeeding and distal sensory polyneuropathy, as well as the modifying effect of ethnicity on this association. Results: Among 767 eligible women, breastfeeding was a protective factor for distal sensory polyneuropathy [adjusted Odds Ratio (OR) = 0.24, 95 % confidence interval (CI) 0.08–0.78; p = 0.019]. Upon adjusting the significant two-way interaction of ethnicity with breastfeeding, a significant reduction in the odds was observed (adjusted OR = 0.02, 95 % CI 0.003–0.17; p = 0.001). Conclusions: The association between breastfeeding and distal sensory polyneuropathy varied by ethnicity, with a strong protective effect observed in Hispanic women. These findings highlight the need for further research and tailored public health strategies in diverse populations.